Association between risk of Alzheimer’s disease and related dementias and angiotensin receptor Ⅱ blockers treatment for individuals with hypertension in high-volume claims dataResearch in context - Sori Kim Lundin; Xinyue Hu; Jingna Feng; Karl Kristian Lundin; Lu Li; Yong Chen; Paul Ernest Schulz; Cui Tao (EBioMedicine)
Summary: Background: Findings regarding the protective effect of Angiotensin II receptor blockers (ARBs) against Alzheimer’s disease and related dementias (AD/ADRD) and cognitive decline have been inconclusive. Methods: Individuals with hypertension who do not have any prior ADRD diagnosis were included in this retrospective cohort study from Optum’s de-identified Clinformatics® Data Mart. We identified antihypertensive medication (AHM) drug classes and subclassified ARBs by blood–brain barrier (BBB) permeability. We compared baseline characteristics and used the Kaplan–Meier (KM) survival curve and adjusted Cox proportional hazards (PH) model for survival analyses. Findings: From 6,390,826 individuals with hypertension, there were 1,839,176 ARB users, 3,366,841 non-ARB AHM users, and 1,184,809 AHM non-users. The unadjusted KM curve showed that ARB users had lower cumulative hazard than other AHM users or AHM non-users (P < 0.0001). In Cox PH analysis, ARB users showed a 20% lower adjusted hazard of developing ADRD compared to angiotensin-converting enzyme inhibitor (ACEI) users and a 29% and 18% reduced hazard when compared to non-ARB/ACEI AHM users and AHM non-users (all P < 0.0001). Consumption of BBB-crossing ARBs was linked to a lower hazard of ADRD development than non-BBB-crossing ARBs, undetermined ARBs, and non-consumption of AHMs by 11%, 25%, and 31% (all P < 0.0001). Interpretation: This study suggests that ARBs are superior to ACEIs, non-ARB/ACEI AHMs, or non-use of AHMs in reducing the hazard of ADRD among patients with hypertension. Also, BBB-permeability in ARBs was associated with lower ADRD incidence. There is no cure for AD, ADRD, or vascular dementia; hence, these findings are significant in preventing those disorders in an inexpensive, convenient, and safe way. Limitations in claims data should be considered when interpreting our findings. Funding: This research was supported by the National Institute on Aging grants (R01AG084236, R01AG083039, RF1AG072799, R56AG074604).